2021
DOI: 10.1021/acsnano.1c10007
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of the Reversible Li-CO2 Batteries over Metal–N4-Functionalized Graphene Electrocatalysts

Abstract: The lack of low-cost catalysts with high activity leads to the unsatisfactory electrochemical performance of Li-CO2 batteries. Single-atom catalysts (SACs) with metal–N x moieties have great potential to improve battery reaction kinetics and cycling ability. However, how to rationally select and develop highly efficient electrocatalysts remains unclear. Herein, we used density functional theory (DFT) calculations to screen SACs on N-doped graphene (SAMe@NG, Me = Cr, Mn, Fe, Co, Ni, Cu) for CO2 reduction and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 63 publications
2
68
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25]37,38 While metallic substances such as Fe, Cr, Mn, Co, Ni, and Cu for SACs have been recently applied to Li-CO 2 battery research and showed improved cell performance, further detailed studies regarding catalyst size effects are needed. 39,40 In this study, we attempted to atomically miniaturize Ir, which is known to be an effective CO 2 evolving catalyst, on highly conductive N-doped carbon nanotubes (NCNTs) to create efficient cathode catalysts for Li-CO 2 cells (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25]37,38 While metallic substances such as Fe, Cr, Mn, Co, Ni, and Cu for SACs have been recently applied to Li-CO 2 battery research and showed improved cell performance, further detailed studies regarding catalyst size effects are needed. 39,40 In this study, we attempted to atomically miniaturize Ir, which is known to be an effective CO 2 evolving catalyst, on highly conductive N-doped carbon nanotubes (NCNTs) to create efficient cathode catalysts for Li-CO 2 cells (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…18–25,37,38 While metallic substances such as Fe, Cr, Mn, Co, Ni, and Cu for SACs have been recently applied to Li–CO 2 battery research and showed improved cell performance, further detailed studies regarding catalyst size effects are needed. 39,40…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals are widely used in various catalytic fields due to their rich con-tent, low cost, and good catalytic activity. Copper was demonstrated effective in the adsorption and activation of CO 2 molecules [52][53][54]. Xu et al prepared copper polyphthalocyaninecarbon nanotubes composites (CuPPc-CNTs) by solvothermal in-situ polymerization method.…”
Section: Carbon Tube-other Metal-based Compositesmentioning
confidence: 99%
“…As is well-known, fast kinetics for CO 2 reduction and evolution reactions (CDRR/CDER) at the cathodes is necessary for the Li-CO 2 batteries . Therefore, various efforts have been directed to developing various efficient catalysts ( e.g ., carbon materials, , metal-based materials, , metal/covalent-organic frameworks, , and redox mediators) . However, despite the great progress that has been made in this regard, Li-CO 2 batteries are still facing severe challenges owing to the large polarization caused by the limited effect of the catalysts.…”
Section: Introductionmentioning
confidence: 99%